Model updating of a helicopter stub wing - Mares, Cristinel; Esperon Miguez, Manuel (International Stress Management Association (ISMA), 2012)
In this paper we describe the process of optimization for the structural model of a helicopter stub-wing based on experimental data. The wing dynamics is updated using the ground vibration tests within the 0-80Hz frequency range and a detailed discussion is carried out to present the modeling errors and the specific finite element analysis leading to an improved dynamic behaviour. Because the main objective for model updating exercises of aeronautical structures is the prediction of the dynamic behavior in flight, as well as the effect of configuration changes, a set of in-flight measurements is determined with the objective to be used for the derivation of a representative model. A preliminary analysis of the model quality to be used subsequently in flight test conditions is carried out.